Zur Ehre Gottes zu musiciren - Krause, A (2017)
My critical writing is closely linked to a pair of oratorios, which are the major ingredients in my final composition portfolio submission, Cantata Eliensis and The Good Samaritan. For my doctoral work I have been researching J. S. Bach's St Matthew Passion in order to inform my compositional endeavours. I am especially driven to write dramatic music and music that tells a story, and the St Matthew Passion is an extended retelling of an enormously dramatic, if brief, story found in the Gospel of Matthew. It is made more interesting by the fact that it is not an outright drama; that is to say, it is not an opera but combines the characteristics both of a drama and of a sermon. This combining of genres directly informs my two dramatic pieces. The bulk of the research into Bach's music became background for my writing here, which focuses not on the specifics of the composition and performances of the St Matthew Passion, but rather on broader research themes of narrative, musical structure, vocality, authorial voice, drama, and vocation as they appear in Bach's work and the work of his musical heirs, as well as in my own composition.